Surfactant Administration During Pediatric Cardiac Extracorporeal Membrane Oxygenation. Issue 4 (May 2019) - Chrysostomou, Constantinos; Maul, Timothy; Istvanic, Filip; Wearden, Peter
Abstract : We investigated the safety and efficacy of surfactant during extracorporeal membrane oxygenation (ECMO) in children with cardiac disease. ECMO patients administered surfactant (surfactant group) were compared with patients who did not receive (control). Criteria to administer surfactant were based on a decreased lung compliance of <0.5 ml/kg/cm H2 O. Efficacy was determined on pulmonary compliance change and the radiography-based respiratory distress severity (RDS) score. For the surfactant group, lung compliance measurements and RDS scores were obtained just before the first surfactant administration (T0), 24 hours after the last dose of surfactant (T1), and 24 hours after ECMO decannulation (T2). For the control group, measurements were obtained at baseline (T0), day of ECMO decannulation (T1), and 24 hours after ECMO decannulation (T2). Eighty were on ECMO, 29 in the surfactant, and 51 in the control group. Surfactant group was younger 20 (6–140) vs. 28 (8–928) days old ( p = 0.03), had longer ECMO duration 110 (58–192) vs. 46 (29–84) hours ( p = 0.001), and had longer mechanical ventilation 16 (11–26) vs. 7 (5–9) days ( p = 0.003). The lung compliance and RDS scores in the surfactant group improved significantly between baseline and 24 hours after decannulation, 0.36 ± 0.13 vs. 0.5 ± 0.12 ml/kg/cm H2 O ( p = 0.002) and 13 ± 3 vs. 12 ± 2 ( p = 0.04), respectively. None developed pneumothorax. Mild pulmonary hemorrhage occurred twice (one in each group). Hospital duration and survival were similar 36 (19–48) vs. 31 (18–48) days and 69% vs. 78% in surfactant and control groups, respectively. Although this is a relatively small study, surfactant appears to be safe in pediatric cardiac ECMO patients.